Modification of the structurally the phase state of aluminum alloy as a result of radiation thermal treatment - Prokhorenko, E.M.; Lytvynenko, V.V.; Bryukhovetskiy, V.V.; Shul’gin, N.A.; Kolodiy, I.V.; Tantsyura, I.G.; Prokhorenko, T.G. (Вопросы атомной науки и техники, 2022)
The effect of relativistic electron beams on the change in the structure of the 2014 aluminum alloy was studied. The mechanical characteristics (hardness, ultimate strength, conditional yield stress) of the samples were measured before and after irradiation. The influence of phase changes on these mechanical characteristics was investigated. The possibility of cleaning the surface of alloy 2014 using electron beams was studied. The identification of phase inclusions in the aluminum alloy was carried out. The changes in the number of phases that occurred as a result of irradiation with relativistic electron beams were determined.